USE OF INTEGRATED DIFFUSION-WEIGHTED MAGNETIC-RESONANCE IMAGING IN PRE-OPERATIVE EVALUATION OF RESECTABILITY OF ADVANCED OVARIAN CANCER - A. E. Solopova; S. K. Ternovoy; V. I. Alipov; A. D. Makatsariya (IRBIS LLC, 2017)
The aim of the study was to compare the diagnostic potential of integrated diffusion-weighted magnetic-resonance imaging (DW-MRI) with multi-spiral computed tomography (MSCT) in pre-operative evaluation of resectability of advanced ovarian cancer. Materials and methods. In the period from February to December 2016, 73 patients with suspected malignant neoplasms of the ovaries underwent preoperative examination, including abdominal/pelvic integrated DW-MRI or MSCT. The DW-MRI test was run using a 1,5 T scanner (b-factors of 0-1000 s/mm2) able to compute the apparent diffusion coefficient (ADC). For each of the two methods, we calculated the peritoneal cancer indices (PCI) and the informational values pertaining to the critical areas of the peritoneal cavity and the pelvis, and compared them with the surgical findings. We used the following criteria to conclude that a surgical intervention would not achieve the optimal cytoreduction: lesions of the omental bursa (> 1 cm); foci in the diaphragm area (> 2 cm); foci on the liver surface (> 2 cm); mesentery lesions of the small and/or large intestine (>1 cm); involvement of para-aortic lymph nodes; metastases to the parenchymal organs (liver, spleen) and the PCI > 20. Results. The sensitivity of DW-MRI vs MSCT was 78,3% vs 50%; and the specificity of DW-MRI vs MSCT was 78% vs 87%, respectively. The DW-MRI based prediction on the impossibility of effective surgical cytoreduction was correct in 92% of patients. The similar figure for MSCT was 64% of patients with inoperable tumors. Conclusion. DW-MRI is an accurate instrument for pre-operative assessment of the involvement of the peritoneum and abdominal organs in the tumor process. Based on this method, it is possible to develop a sensitive and specific algorithm for evaluating the resectability of ovarian cancer, thus avoiding unnecessary surgical intervention.